Pattern Engineering for Customized Women Seamless Ballistic Protection Vest on 3D Virtual Mannequin (Journal of Fiber Bioengineering and Informatics, 2023)
There has been a significant increase in the number of women involved in various security duties. However, they mostly wear men's ballistic vests with smaller sizes, which bring poor ballistic protection performance, less comfort, and negative psychological effects. In recent decades, considerable efforts have also been made to improve the overall performance of ballistic protective vest for women. However, a ballistic vest that properly adjusts the chest area for different morphologies to provide a goodfit, comfort, and better ballistic protection is very important and in high demand. Our current research study introduces a new 2D-3D-2D pattern re-engineering design method and automatic pattern generation on the adaptive 3D virtual mannequin to develop the first and multi-layer pattern for a seamless women ballistic vest. The method mainly eliminates the inclusion of darts to achieve the required breast volume with better fit and most importantly satisfactory ballistic protection.